Safety of different electrocautery modes for endoscopic sphincterotomy: a Bayesian network meta-analysis. (December 2021) - Hedjoudje, Abdellah; Cheurfa, Chérifa; Farha, Jad; Jaïs, Bénédicte; Aubert, Alain; Lorenzo, Diane; Maire, Frédérique; Badurdeen, Dilhana; Kumbhari, Vivek; Prat, Frédéric
Background and aims: Post-endoscopic retrograde cholangiopancreatography acute pancreatitis (PAP) and post-sphincterotomy hemorrhage are known adverse events of post-endoscopic retrograde cholangiopancreatography. Various electrosurgical currents can be used for endoscopic sphincterotomy. The extent to which this influences adverse events remains unclear. We assessed the comparative safety of different electrosurgical currents, through a Bayesian network meta-analysis of published studies merging direct and indirect comparison of trials. Methods: We performed a Bayesian random-effects network meta-analysis of randomized controlled trials that compared the safety of different electrocautery modes for endoscopic sphincterotomy. Results: Nine studies comparing four electrocautery modes (blended cut, pure cut, endocut, and pure cut followed by blended cut) with a combined enrollment of 1615 patients were included. The pooled results of the network meta-analysis did not show a significant difference in preventing post-sphincterotomy pancreatitis when comparing electrocautery modes. However, pure cut was associated with a statistically significant increased risk of bleeding compared with endocut [relative risk = 4.30; 95% confidence interval (1.53–12.87)]. On the other hand, the pooled results of the network meta-analysis showed no significant difference in prevention of bleeding when comparing blended cut versus endocut, pure cut followed by blended cut versus endocut, pure cut followed by blended cut versus blended cut, pure cut versus blended cut, and pure cut versus pure cut followed by blended cut. The results of rank probability found that endocut was most likely to be ranked the best. Conclusion: No electrocautery mode was superior to another with regard to preventing PAP. Endocut was superior with respect to preventing bleeding. Therefore, we suggest performing endoscopic sphincterotomy with endocut.